2014
DOI: 10.1097/md.0000000000000200
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Blinding With a New Pragmatic Placebo Needle

Abstract: Placebo control is a useful method for determining the efficacy of a therapy. In acupuncture researches, the preferred method for placebo control is acupuncture using a placebo needle that has a blunt tip and achieves no skin penetration.We performed a crossover study to validate the blinding effect of a new type of placebo needle. Sixty volunteers were randomized to receive acupuncture using 2 types of needles with different sequences: sequence AB, involving first the pragmatic placebo needle and then the rea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
38
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 45 publications
(38 citation statements)
references
References 21 publications
0
38
0
Order By: Relevance
“…However, owing to the characteristics of acupuncture, it is hard to use a placebo needle on patients. Based on a randomised controlled cross-over trial, the SA that will be implemented in this study will serve as a valid control25 because it can produce a good blinding effect to patients from two groups. This might balance the placebo effect between the two groups and reveal the efficacy of acupuncture for DLSS.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, owing to the characteristics of acupuncture, it is hard to use a placebo needle on patients. Based on a randomised controlled cross-over trial, the SA that will be implemented in this study will serve as a valid control25 because it can produce a good blinding effect to patients from two groups. This might balance the placebo effect between the two groups and reveal the efficacy of acupuncture for DLSS.…”
Section: Discussionmentioning
confidence: 99%
“…Thrusting and twisting motions will be used by acupuncturists to simulate the treatment and aid in blinding the patients. The sham needle used in this trial had a blunt tip similar to the Streitberger needle,24 which has been proven as a useful placebo control 25. Each placebo needle consists of four parts: the needle handle, needle body, blunt tip and adhesive pad (an illustration of the placebo needle used in this trial is shown as figure 2).…”
Section: Interventionmentioning
confidence: 99%
“…Since sham control is a useful method for determining the effectiveness of a therapy, we will choose a sham needle [12] that has a blunt tip and achieves no skin penetration. To apply the sham needles produces a good subject blinding effect, the reason of which is that they have a similar appearance to conventional acupuncture needles, however, without skin penetration.…”
Section: Methods and Designmentioning
confidence: 99%
“…We are also curious about this question, and we designed the sham acupuncture to use a blunt-tip needle on acupoints without penetration. According to the findings of our prior crossover study, this non-insertion-type needle is a valid sham control for acupuncture research and can achieve good subject blinding effects with a similar appearance to traditional acupuncture [39]. Given a sufficiently thin needle and the manipulation used (lifting, thrusting or rotating), even blunt tips can make participants feel the sensation of piercing.…”
Section: Discussionmentioning
confidence: 99%
“…Given a sufficiently thin needle and the manipulation used (lifting, thrusting or rotating), even blunt tips can make participants feel the sensation of piercing. Most of the participants were hardly able to distinguish this device from real acupuncture in the previous trial [39]. In addition, in the current trial, we will use BL 23, BL 33, BL 35 and SP 6 as the selected acupoints instead of conception vessel 1 (CV 1) and CV 4.…”
Section: Discussionmentioning
confidence: 99%